DEVELOPMENT OF FRAME ELEMENT FOR NONLINEAR FINITE ELEMENT ANALYSIS OF REINFORCED CONCRETE SHEAR WALLS CONSIDERING SHEAR DEFORMATION - ภัคพิตรพิบูล ธรรมการ (Srinakharinwirot University Engineering Journal, 2018)
This paper presents analytical procedures of the flexibility-based for the nonlinear analysis of frame elements with shear deformation developed to model the behavior of RC shear walls which can fail suddenly at lower ductility levels. An analytical procedure was developed for plasticity sectional response analysis modeling based on smeared crack approaches by section discretization into layers. The plasticity sectional analyses were made to capture shear mechanisms in a section of concrete, with the inclusion of nonlinear Poisson effects, softening effect of concrete, tension stiffening, as well as confining effects for out-of-plane steel reinforcement and especially with dowel action. Based on flexibility method, element forces were obtained by performing equilibrium-based numerical integration on section behaviors along the length of the elements. Verification of the accuracy of the procedure was undertaken with six specimens. A good fit between experimental and theoretical results provided by the model was obtained.